A construction technique using closed hollow ceramic elements, typical of historical buildings in Calabria. Issue 3 (2nd September 2017) - Gattuso, Caterina
ABSTRACT: In the south of Italy it is still possible to find ancient buildings whose vaults are constructed with aggregated single hollow ceramic elements locally known as 'caruselli'. This particular system differs from other types of hollow brickwork in the way its elements are aggregated. Arranged in progressively staggered rows, the 'caruselli' are joined laterally and simply binded with mortar in the interstices. As a result, the structure is quite light and can reach considerable sizes. As a matter of fact, the archaeological area of Crotone, Calabria (Italy) was found to host a farm where several buildings had vaults characterized by these ceramic elements; these buildings were examined in order to obtain further knowledge about this construction system. This study, focusing mainly on the analysis of the constituent materials and their chemical and physical properties, allowed us to obtain information so as to better comprehend their historical and archaeological values, production processes and deterioration phenomena, and identify appropriate and efficient preservation actions.